Incorporating the patient-centered approach into clinical practice helps improve quality of care in cases of hypertension: A retrospective cohort study - Nida Buawangpong (2020)
© 2020 The Author(s). Background: Treating hypertensive patients by integrating the patient-centered approach would influence the practice and outcome of treatment. Our purpose was to determine whether the implementation of a patient-centered approach in health care delivery can improve adhering to guidelines and the quality-of-care. Methods: A retrospective study was conducted using secondary data from the electronic medical records of the patients treated in the two primary care outpatient settings at the Family Medicine (FM) and Social Security (SS) clinics. A key feature of the FM clinic is the incorporation of a patient-centered approach in its service delivery. Individual information regarding initial assessment and treatment at the follow-up visits was reviewed for 1 year. Comparison of adherence to treatment guidelines between the two primary care clinics was performed by using chi-square, Fisher's exact test or a t-test. To explore the difference in blood pressure and BP control between the two clinics, linear and logistic regression analysis respectively were performed with an adjustment for CV risk score in 2016 as a key confounder. Results: The evidence included 100 records from each clinic, showed variation between the two primary care sites. The FM clinic had more complete records regarding family history of hypertension, assessment for secondary causes, prescription for lifestyle modification and appropriate adjustment of medication. Higher levels of blood pressure control were recorded in the FM clinic, specifically systolic pressure 2.92 mmHg (p = 0.073) and diastolic pressure 5.38 mmHg (p < 0.001) lower than those recorded in the SS clinic. There was a 2.96 times higher chance for BP goals to be achieved in patients in receipt of hypertensive care at the FM clinic (p = 0.004). Conclusions: Adopting a patient-centered approach in service delivery could improve the quality of care for hypertension patients in primary care in Thailand.